Static and dynamic properties of the turbocharged diesel with changing advance angle of injection of fuel - Левчук, В. І.; Арендаренко, В. М.; Іванов, О. М. (Scientific Progress & Innovations, 2012)
The results of experimental studies of the effect of advance angle of fuel injection on the static and dynamic properties of a diesel engine with a turbocharger have been produced. The degree of influence of the controlled parameter on the static properties of a diesel engine was assessed on the basis of velocity characteristics of operating parameters of diesel at different advance angles of fuel injection. From the analysis of dynamic modes of the free acceleration of a diesel engine, produced by various characters of changing of the advance angle of fuel injection, conclusions about the close relationship between the onset of the fuel supply and the quality of a given transition have been made.